Cortical columns - Molnár, Z (Elsevier, 2013)
Modularity is a common organizational principle in all parts of the brain. The cerebral cortex exhibits a laminar and radial organization. Cortical columns are sometimes regarded as the basic functional units in cerebral cortical processing, development, and evolution. Cortical column is a historic term that can refer to a vertically arranged cell constellation, a pattern of connectivity, myelin distribution, metabolic characteristics, staining property, vasculature, magnitude of specific gene expression, embryonic origin, or functional properties. The columnar organization reflects the intermittently recursive mapping of several variables under the two-dimensional surface of the neocortex in a variably independent or combined (e.g., hypercolumn) manner. The term cortical column is constantly evolving with the improved understanding of the organization and function of the various radially oriented groups of cells that share certain functional or anatomical properties. In this chapter, the following points are discussed and examined: (1) the problems associated with the current nomenclature; (2) the evidence for and against the idea that columns are the common building blocks of the cortex; (3) the question of how constant the cell numbers are within a column and how homogeneous is the structure of the various columns; (4) the possible functions of the columns; and (5) the current knowledge of the columnar development in the cortex. Knowledge of the laminar and columnar organization of the cerebral cortex is continuously advancing, and with this the conceptual details of the columnar organization also is changing. The time may arrive when both the concept and the nomenclature will have to adapt to these changes.